SOCIAL LOAFING DAN TURNOVER INTENTION PADA KARYAWAN PT. TELEKOMUNIKASI INDONESIA, TBK (CABANG MEULABOH) - Jannah, Wardatul; Hidayat, Muhammad Rahmat; Zhafira, Nabila Hilmy; Putra, Zainal (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This study aims to analyze the influence of social laziness on the intention to leave work at PT. Telekomunikasi Indonesia Meulaboh branch. The variables in this study are; (1) Social Loafing, (2) Turnover Intention. From a population of 369 people, 168 people were sampled using a simple random sampling method. The Model Summary shows an R value of 0.299, an R Square of 0.089, an Adjusted R Square of 0.072, and a Standard Error of the Estimate of 16.52891. The results showed that social laziness significantly affected the intention to leave the job. Based on these findings, it is recommended that PT. Telekomunikasi Indonesia Meulaboh branch increases transparency and fairness in decision-making, reduces social laziness by clarifying individual responsibilities, and develops a more empathetic and supportive leadership style. These measures are expected to create a healthier and more supportive work environment, thereby reducing the employee's intention to leave work.